2022
DOI: 10.1111/dth.15596
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of combined oral minocycline and narrowband UVB phototherapy in vitiligo: A randomized, double‐blind, placebo‐controlled trial

Abstract: Narrowband ultraviolet B (NBUVB) phototherapy is an effective therapeutic option for generalized vitiligo. Previous reports showed the potential benefit of minocycline to stop disease progression in vitiligo. Meanwhile, minocycline has antioxidative, anti-inflammatory, and immunomodulating properties. There is no clinical study combining oral minocycline and NBUVB for treating generalized vitiligo. This study aims to compare the efficacy and safety of the combination treatment of NBUVB plus oral minocycline wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Side effects were reported by 14.2% of minocycline users, including oral mucosal pigmentation, gastrointestinal complaints, and headaches 24 . However, the other study demonstrated that the combination of minocycline and NB‐UVB was slightly more effective than NB‐UVB alone, with a higher percentage improvement in VASI scores compared to the monotherapy group 25 …”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Side effects were reported by 14.2% of minocycline users, including oral mucosal pigmentation, gastrointestinal complaints, and headaches 24 . However, the other study demonstrated that the combination of minocycline and NB‐UVB was slightly more effective than NB‐UVB alone, with a higher percentage improvement in VASI scores compared to the monotherapy group 25 …”
Section: Resultsmentioning
confidence: 94%
“…9 All studies that have investigated the effect of minocycline on vitiligo lesions have reported a significant improvement in the lesions. 9,[22][23][24][25] However, in one study, no significant difference was observed between the group receiving minocycline and the group receiving OMP. 23 In another study, its effectiveness was reported to be less than phototherapy.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The addition of oral minocycline to NBUVB treatment did not improve efficacy and also induced drug-induced hyperpigmentation. 113…”
Section: Minocyclinementioning
confidence: 99%